Determination of lethal dose and growth reduction of EMS and sodium azide treated dragon fruit (Hylocereus spp.) cultivars - G, PAVITHRA; G, KARUNAKARAN; N P, SIVARAMAKRISHNA V; T, SAKTHIVEL; M, ARIVALAGAN; D C, LAKSHMANA REDDY; P C, TRIPATHI; T, RUCHITHA (The Indian Journal of Agricultural Sciences, 2024)
An exotic vine cactus, dragon fruit (Hylocereus spp.) commonly known as ‘pitaya’ is a weather resilient crop, rich in vitamin C and antioxidants. The chances of crop improvement through conventional breeding is a limitation in dragon fruit, hence induced mutation can be exploited for creating genetic variability. The present study was carried out during 2019 to 2022 at Central Horticulture Experimental Station (ICAR-Indian Institute of Horticultural Research, Bengaluru, Karnataka), Hirehalli, Karnataka to induce the variability in two dragon fruit cultivars, viz. Hirehalli Red and Hirehalli White. The experiment was laid out in completely randomized design (CRD) comprises of 15 treatments with different dosage of EMS (Ethyl Methane Sulphonate) (0.2%, 0.5%, 0.8%, 1.5%, 2%, 2.25%, 2.50%, 2.75% and 3.00%) and sodium azide (0.02%, 0.03%, 0.04%, 0.05% and 0.06%) and untreated seeds were sown as control with 3 replications of each. The outcome of the variance analysis showed highly significant difference (P<0.05) for the evaluated traits. The lethal doses (LD50) for EMS in Red was 2.685% and in White was 2.791%. Mutagenesis with sodium azide showed the lethal doses (LD50) of 0.052 and 0.053% in Red and White cultivars, respectively. The GR50 value in the cv. Red was 0.68, 0.86, 0.48% and in White was 0.98, 1.08 and 0.89% for seedling height, shoot and root length, respectively. The determined LD50 and GR doses obtained from this research can be exploited in mutation breeding programme of dragon fruit to develop a cultivar with novel traits.